The Main Problems of Housing for Indigent Households in Poland and the Changes Perspective - Rataj, Zuzanna (Studia Oeconomica Posnaniensia, 2017)
The paper discusses the main issues of housing for indigent households in Poland, and the possibility of changes. On the basis of national research the paper shows the possibility of solutions of parts of the difficulties, such as the shortage of social housing, the lack of a legal title to rented housing, or the excessive backlog of charges for the use of residential premises. Based on the best proven practices from different cities the paper discusses the chances of development in social housing.